Business-State Relations under PT Governments: Participatory Policy-Making in Brazil - Schmitt, Stefanie Tomé (2021)
The thesis addresses the impacts of participatory policy-making on business political action during the Partido dos Trabalhadores (PT) - Workers Party, Governments in Brazil. Its focus relies on the mechanisms of participation, known in Portuguese as \'órgãos colegiados\' - collegiate bodies, joined by the peak sectoral corporatist business associations of agriculture, commerce, industry and financial services. Research depicts the rule configuration of 125 collegiate bodies operational at the federal level and traces the policy process in three cases, in which business was empowered to influence policy outcomes. In-depth analysis explores deliberative moments, assessing the extent that collective deliberations included and engaged business in policy-making, formalizing business political action. Whereas business was overrepresented in 65% of the collegiate bodies with information about membership, engendering a more formalized pattern of business politics relied not only on choices of institutional design that promoted business inclusiveness in participatory policy-making, but also on the levels of commitment building achieved by business and government representatives within mechanisms of participation and in related policy networks. Even though collegiate bodies increased the organization of the policy process, they formalized business political action to the extent that business perceived them as political activities that could generate greatest returns. As such, apart from institutional choices, formalization depended on the capabilities within the political system, and the preferences arising from them, that compounded the informational sets of business and government representatives and influenced their actions regarding participatory policy-making between 2003 and 2016.